(untitled) (Globish: An English-Indonesian Journal for English, Education, and Culture, 2020)
This study investigated the influence of guided writing materials in studentsâ€™ writing ability at English Study Program FKIP UR in which forty students that simple randomly selected at English Study Program FKIP UR. The instruments used were questionnaire and writing test. Based on the research findings, the responses of questionnaire were coded into interval score by using Likert Scale which showing the studentsâ€™ ability and their opinion in guided writing that consisted of fifteen statements based on six indicators in the form of frequency. On the other side, writing test administered in term of finding the studentsâ€™ writing ability. It was a writing outlining with fifteen listed in the form of brief statements. Before the research revealed, the tried out had been applied in assessing the validation of the instrument by using Pearson Product Moment correlation formula indicated that items were valid. Reliability calculation were performed in Cronbachâ€™s Alpha denoted that the instrument was reliable. The instrument can be stated reliable when if it has Cronbach Coefficient is higher than 0.60. based on research findingsm it can be concluded that: first, the studentsâ€™ writing by using guided writing was categorized into good category 56.2, second, the mean score of studentsâ€™ writing test is 50.68, it can be stated that studentsâ€™ writing ability is categorized into good category. While Fcount is 27.78 and FtableÂ is 4.25. Based on its criteria, H0 is accepted if Ftable < Fcount and Ha is accepted if Fcount > Ftable. After it compared (27.78 > 4.25), it showed that H0 is rejected. It can be concluded that there was significant influence of guided writing in studentsâ€™ writing ability.